2021
DOI: 10.2174/1871526520666200106121839
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Study of Anti-leishmanial Effect of Naja naja oxiana Snake Venom on Leishmania major

Abstract: Background: Although a majority of patients with cutaneous leishmaniasis (CL) are healed with Glucantime chemotherapy, the increased drug resistance rate following its consumption is a concern. In this study , Naja naja oxiana crude venom of cobra snakes was used for the first time as an assembled combination of bioactive pharmaceutical components on Leishmania major (L. major) standard strain . Objective: To evaluate the efficacy of the Naja naja oxiana crude venom of Iranian cobra snakes on Leishmania m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…So far, antiprotozoal activity has been found in snake venoms from various families and genera, including Asian elapids, as well as Asian, African and American viperids, and Colubrid [ 3 , 8 ]. Together with recent findings [ 12 , 13 , 14 , 15 ], these data suggest that antiprotozoal activity may be a widespread property of snake venom.…”
Section: Introductionsupporting
confidence: 84%
“…So far, antiprotozoal activity has been found in snake venoms from various families and genera, including Asian elapids, as well as Asian, African and American viperids, and Colubrid [ 3 , 8 ]. Together with recent findings [ 12 , 13 , 14 , 15 ], these data suggest that antiprotozoal activity may be a widespread property of snake venom.…”
Section: Introductionsupporting
confidence: 84%
“…In particular, they include phospholipases A2 [6], L-amino acid oxidases [7] and cathelicidins [8]. Venoms of several snake species were shown to be toxic to protozoans [9][10][11][12] and identification of proteins manifesting anti-protozoan activity in viperid venoms revealed that phospholipase A2 [22], metalloproteinase [23], L-amino acid oxidase [24] and disintegrin [14] are toxic to different protozoa. For example, BnSP-7 toxin, a catalytically inactive phospholipase A2 from Bothrops pauloensis snake venom, showed activity against promastigote Leishmania amazonensis parasite forms, inhibiting parasite proliferation by 60-70% at toxin concentrations of 50-200 µg/mL 96 h after treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the data about influence of cobra venom on protozoa were very limited. Thus, it was shown that N. haje venom exerted a significant growth inhibition of Trypanosoma cruzi and Leishmania donovani infantum parasites [25] and the venom of N. oxiana revealed remarkable anti-leishmanial effects [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations